Continuous‐Flow Hydrogenation and Reductive Deuteration of Nitriles: a Simple Access to α, α‐Dideutero Amines. Issue 10 (18th September 2019) - Mészáros, Rebeka; Peng, Bai‐Jing; Ötvös, Sándor B.; Yang, Shyh‐Chyun; Fülöp, Ferenc
Abstract: A simple and efficient continuous flow methodology has been developed for hydrogenation and reductive deuteration of nitriles to yield primary amines and also valuable α, α‐dideutero analogues. Raney nickel proved to be a useful catalyst for the transformation of a wide range of nitriles under reasonably mild conditions with excellent deuterium incorporation (>90 %) and quantitative conversion. Among known model compounds, three new deuterated primary amines were prepared. The large‐scale synthesis of deuterated tryptamine was also carried out to deliver 1.1 g product under flow conditions. Abstract : Go with the flow : A continuous flow methodology for the hydrogenation and reductive deuteration of nitriles can be used for the synthesis of primary amines and valuable α, α‐dideutero analogues. This methodology can be used for the gram‐scale synthesis of deuterated tryptamine.